Impact of Phenomenon-Based Learning on High School Physics Education in Shymkent, Kazakhstan - Bayan Ualikhanova; Ganya Ormanova; Dauletbay Berdaliyev; Nurken Mussakhan; Bakdaulet Anas; Ertan Güdekli (Qubahan Academic Journal)
Traditional teaching methods have become obsolete in modern society, and require people with high efficiency, cooperation, and active participation. Consequently, a new approach to education should provide necessary information and abilities for further progress on a global scale. This study aims to examine the beneficial effects of using phenomenon-based learning (PhBL) as a pedagogical approach for teaching physics to high school students in Shymkent, the Republic of Kazakhstan. The research also aims to examine the influence of PhBL on students’ motivation to study physics and improve their knowledge of the subject. The fundamental approach to teaching physics was to introduce lessons through phenomena and use interdisciplinary communication as a universal approach. In addition, a survey was conducted to determine the rationale for the interaction of students with physics both in the academic environment and in practical use as well as to assess the longevity of these acquired abilities in the memory of students. The results show that the introduction of PhBL led to an enhancement in student performance, with an increase of more than 10%. This indicates the high efficiency of the proposed approach. In addition, the introduction of phenomenon-based learning contributes to an increase in retention and stable assimilation of information received over a long period. The use of PhBL to teach physics through interdisciplinary courses significantly improves students’ skills and contributes to long-term preservation of their acquired abilities.